Impact of spiritual values on tourists’ psychological wellbeing: evidence from China’s Buddhist mountains - Ge Zhang; Keji Huang; Shiwei Shen (Frontiers in Psychology, 2023)
Spiritual values can be a source of meaning for people, and can also determine their feelings, behavior, and mental health. In China’s Buddhist mountains, we collected a total of 400 valid questionnaires from Mount Putuo and Mount Jiuhua, and identified spiritual values as transcendence, general connectedness, inner balance, positive life direction, and special religious feelings. We also explored the impact of these spiritual values on tourists’ psychological wellbeing according to the PERMA model (positive emotion, engagement, relationships, meaning, and achievement). The results revealed that the more easily attained spiritual values (general connectedness, positive life direction, and special religious feelings) had a greater influence on psychological wellbeing than the less easily-attained spiritual values (transcendence and inner balance). Positive emotion and meaning, as components of psychological wellbeing, were strongly influenced by the four spiritual values, whereas engagement, accomplishment, and relationships were influenced by fewer spiritual values. The research contributes to the existing knowledge on spiritual values by analyzing their dimensions and relationships with tourists’ wellbeing from different levels, and also provides empirical suggestions for the sustainable development of religious tourism destinations.